2014
DOI: 10.3390/ijerph110706979
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobes and Bacterial Vaginosis in Pregnancy: Virulence Factors Contributing to Vaginal Colonisation

Abstract: The aetiology and pathogenesis of bacterial vaginosis (BV) is unclear but it appears to be associated with factors that disrupt the normal acidity of the vagina thus altering the equilibrium between the normal vaginal microbiota. BV has serious implications for female morbidity, including reports of pelvic inflammatory disease, adverse pregnancy outcomes, increased susceptibility to sexually transmitted infections and infertility. This paper reviewed new available information regarding possible factors contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 153 publications
(230 reference statements)
0
68
1
2
Order By: Relevance
“…vaginalis has shown high sensitivity (100%) but low specificity (49%) for BV. It is often detected in the absence of BV as well as in both sexually inexperienced and experienced women (54,55). Numerous studies have confirmed the presence of G. vaginalis not only in women with BV but also in women without BV, via both conventional culture techniques and molecular-based studies (11,56).…”
Section: Gardnerella Vaginalismentioning
confidence: 97%
See 2 more Smart Citations
“…vaginalis has shown high sensitivity (100%) but low specificity (49%) for BV. It is often detected in the absence of BV as well as in both sexually inexperienced and experienced women (54,55). Numerous studies have confirmed the presence of G. vaginalis not only in women with BV but also in women without BV, via both conventional culture techniques and molecular-based studies (11,56).…”
Section: Gardnerella Vaginalismentioning
confidence: 97%
“…Both culture-and DNA-based studies have detected these genera in both women with and those without BV (4,9,14,20,54,57,82,87). Delaney and Onderdonk reported that the bacterial concentration of Peptostreptococcus increased significantly as the total Nugent score increased.…”
Section: Anaerobic Coccimentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial vaginosis is more frequent in females with bacterial infection of caries [35]. Total spending on dental services in the United States will be over $65 billion this year, with arguably about half of this a direct or indirect result of dental caries [36].…”
Section: Epidemiologymentioning
confidence: 99%
“…Dysbiosis is broadly observed for several microbial ecologies, including in aquatic systems or intestinal systems. It has been shown to be associated with illnesses, such as cancer [30,31], bacterial vaginosis [32], inflammatory bowel disease [33,34], chronic fatigue syndrome [35], obesity [36,37] and colitis [38]. Dysbiosis in the gut is known to be associated with major chronic inflammation states [39].…”
Section: Dynamics Of the Competition Model M2 In Response To The Immumentioning
confidence: 99%